Polyimide: compositions, methods of making, and parts made therefrom
By using ODA, PMDA, PPD and BPDA monomers to prepare polyimide particles, the problem of insufficient toughness in existing polyimide materials is solved, forming a polyimide composition with high toughness and high density, which is suitable for manufacturing parts such as clutch rollers, improving the performance and durability of the parts.
Patent Information
- Application Number
- CN202480040114.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-06-16
- Filing Date
- 2024-06-14
- Publication Date
- 2026-01-23
AI Technical Summary
Existing polyimide materials lack sufficient toughness when manufacturing parts such as clutch rollers, leading to premature failure under harsh conditions and failing to meet the requirements of higher performance and more demanding applications.
Using polyimide polymer particles containing monomers derived from ODA, PMDA, PPD, and BPDA, a polyimide composition with an apparent density ≤0.25 g/cm³ is formed through specific synthesis and processing methods, enhancing its toughness and density, and molding parts at high temperatures.
It improves the toughness and density of polyimide parts, extends their service life, enhances their anti-friction and lubrication properties, enables them to withstand greater stress, and significantly improves the performance of the parts.
Smart Images

Figure CN121399185A_ABST
Abstract
Description
Cross Reference to Related Applications
[0001] No TECHNICAL FIELD
[0002] The present invention relates generally to polyimide compositions, parts made from polyimide compositions, and methods of making polyimide compositions and parts. BACKGROUND
[0003] Parts made from polyimide compositions are known. For example, parts have been made from polyimide compositions derived from 4,4' oxydianiline (ODA) and pyromellitic dianhydride (PMDA), and from p-phenylenediamine (PPD), m-phenylenediamine (MPD), and biphenyltetracarboxylic dianhydride (BPDA), respectively. However, as the demand for higher performance and more demanding applications continues to increase, the limitations of polyimides derived from these polyimides have become apparent. For example, in some applications, it is desirable to increase the toughness of parts derived from these polyimide compositions. An increase in toughness means an increase in product life. Higher toughness of polymers also provides design engineers with greater flexibility in designing parts to withstand more challenging operating conditions than can be possible with brittle polymers.
[0004] One such application where an increase in toughness of polyimide parts is desirable is in clutches for main and secondary transmissions. Polyimides can be shaped into rollers that can be used in clutches (clutch rollers). As the power of engines increases, the pressure on clutch rollers made from existing polyimide materials also increases, and these more demanding conditions have resulted in some polyimide parts failing earlier than desired, resulting in costly repair expenses.
[0005] Accordingly, there is a need for new polyimide compositions and methods of making polyimide compositions that provide improved toughness when shaped into parts such as clutch rollers. SUMMARY
[0006] The present invention relates to a polyimide composition comprising particles of a polyimide polymer derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein the polyimide composition has an apparent density of < 0.25 grams per cubic centimeter when the polyimide composition consists of the particles of the polyimide polymer.
[0007] The present invention further relates to a method of making a polyimide composition, the method comprising combining (i) ODA, (ii) PMDA, (iii) PPD, (iv) BPDA, and (v) a solvent at a time and under conditions sufficient to form a reaction product mixture comprising a polyamide and a solvent; heating the reaction product mixture at a temperature of > 110 °C and for a time sufficient to form solid polyimide particles and remove water; filtering and washing the formed solid polyimide particles to form washed solid polyimide particles; and drying the washed solid polyimide particles to form a polyimide composition comprising dried polyimide particles having an apparent density of less than 0.25 g / cm3. 3
[0008] The present invention still further relates to a part formed from a polyimide composition comprising particles of a polyimide polymer derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein the polyimide composition has an apparent density of < 0.25 grams per cubic centimeter when the polyimide composition consists of particles of the polyimide polymer.
[0009] The present invention provides polyimide compositions that can be shaped into parts having increased toughness and density and provide extended life in applications with the ability to withstand greater stresses in typical use. The present invention further provides polyimide compositions having improved resistance to friction or lubricity properties. BRIEF DESCRIPTION OF DRAWINGS
[0010] Figure 1 Representative friction and wear test materials machined to a specific shape and size for testing on a Falex instrument.
[0011] Figure 2 Representative tensile strength of sintered parts plotted against % BPDA and % PPD in the polymers tested. Open symbols represent polymer compositions formed by blending BPDA-PPD homopolymers and PMDA-ODA homopolymers in different ratios. Filled symbols represent different copolymeric polyimide compositions of the present invention. The tensile strength of the copolymers is significantly higher than the blended polymers with the same monomer composition.
[0012] Figure 3 The elongation at break of sintered parts is plotted against the BPDA and PPD in the polymer tested. Open symbols represent polymer compositions formed by blending BPDA-PPD homopolymers and PMDA-ODA homopolymers in different ratios. Filled symbols represent different copolymeric polyimide compositions of the invention. The elongation of the copolymers is significantly higher than the blended polymers with the same monomer composition.
[0013] Figure 4 The polymer toughness of sintered parts is plotted against the BPDA and PPD in the polymer tested. Open symbols represent polymer compositions formed by blending BPDA-PPD homopolymers and PMDA-ODA homopolymers in different ratios. Filled symbols represent different copolymeric polyimide compositions of the invention. The toughness of the copolymers is significantly higher than the blended polymers with the same monomer composition. DETAILED DESCRIPTION
[0014] As used herein, “BPDA” means biphenyl tetracarboxylic dianhydride; PMDA means pyromellitic dianhydride; “PPD” means p-phenylene diamine; and “ODA” means 4,4’-oxydianiline.
[0015] “Homopolymer” as used herein with respect to polyimides means a polymer formed from the reaction of a dianhydride and a diamine having the same repeating unit throughout the polymer backbone.
[0016] A polyimide composition comprising: polyimide particles derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein the polyimide composition has an apparent density of < 0.25 grams per cubic centimeter when the polyimide composition consists of particles of polyimide polymer.
[0017] ODA, PMDA, PPD, and BPDA are as defined above.
[0018] A polyimide is a polymer comprising repeating units having imide functionality. One of skill in the art will know what a polyimide and imide functionality are. The polyimide particles are derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, as described, for example, below with respect to the method of producing the polyimide composition. One of skill in the art will know how to obtain the polyimide particles based on the method described below. The size, shape, and morphology of the polyimide particles can vary depending on the ratio of monomers used and the conditions used in the method. One measure of the size, shape, and morphology of the polyimide particles is the apparent density. The polyimide particles have an apparent density of less than 0.25 g / cm 3, alternatively 0.10 g / cm 3 to 0.25 g / cm 3 , alternatively 0.15 g / cm 3 to 0.25 g / cm 3 , alternatively 0.10 to 0.20 g / cm 3 Apparent density is measured as described in the Examples and is for polyimide particles without added filler or any other additives. For example, the apparent density of polyimide particles can be measured using a volumeter following the test method described in ASTM-D1895-17, entitled “Standard Test Methods for Apparent Density, Bulk Factor, and Pourability of Plastic Materials.”
[0019] Adding filler can change the apparent density, and thus the apparent density of the polyimide composition. Thus, when a filler is included in the polyimide composition, the apparent density refers to polyimide particles derived from the same monomer ratio and using the same method and conditions but without the addition of any filler. The apparent density is considered a measure of the particle morphology, which affects the ability of the polyimide particles to form tough parts having sufficient specific gravity.
[0020] As used herein, “when the polyimide composition consists of particles of polyimide polymer” means that the polyimide composition contains only particles of polyimide polymer, in addition to residual materials such as unreacted reactants and / or impurities, and does not contain other added materials. The polyimide particles and / or polyimide composition can include additional materials, such as fillers. However, when the polyimide composition includes a filler, it has an apparent density of < 0.25 grams per cubic centimeter if the particles and / or polyimide composition are made without the use of the filler but using the same monomers, monomer ratios, conditions, and processes as used to make the polyimide composition containing the filler.
[0021] In one embodiment, the toughness of a part made from a polyimide composition is greater than a part made from a mixture of polymers A) and B), where polymer A) is derived only from ODA and PMDA monomers, and polymer B) is derived only from PPD and BPDA monomers, and where the molar ratios of ODA, PMDA, PPD, and BPDA in the part made from the polyimide composition are the same as in the mixture of homopolymer A) and homopolymer B).
[0022] As used herein, "part" has the meaning as typically known in the art. In one embodiment, the part is a clutch roller. Examples of parts include, but are not limited to, a seal ring, a spherical washer, a compressor seal, a ball bearing retainer, a planetary gear set washer for electric vehicles, a drive washer for replacement of metal thrust needle bearing, a main bearing or lower bearing in scroll compressors for heating and air conditioning applications, a valve seat or poppet valve in high pressure gas valves, a friction or wear component in a wind turbine, and a variable stator vane (VSV) or variable inlet guide vane (VIGV) in a compressor of a jet engine. The parts can be used in the aerospace, transportation, and industrial fields. The polyimide composition of the present invention can be used as a sealing device in electrochemical cells such as lithium batteries. The parts can be manufactured by methods known in the art. Those skilled in the art will know how to mold the polyimide composition to form the parts.
[0023] Toughness of a material and / or part is defined by its ability to absorb energy and plastically deform without fracturing. It is also defined as the amount of energy per unit volume that a material can absorb before breaking. Yet another definition is the ability of a material to provide resistance to fracture when a stress is applied. Toughness is determined by calculating the area under the stress-strain curve, where the y-axis is stress and the x-axis is strain. Those skilled in the art will know how to determine the stress and strain of a part manufactured from the polyimide composition. For the purposes of the present invention, the toughness of a tensile dog bone bar under tensile stress is determined and reported. The tensile stress-strain curve of the polyimide dog bone shape is obtained using an Instron testing machine. The toughness is obtained by numerically integrating the area under the stress-strain curve and reported in Ksi.
[0024] A method of manufacturing a polyimide composition comprising:
[0025] combining (i) ODA, (ii) PMDA, (iii) PPD, (iv) BPDA, and (v) a solvent under time and conditions sufficient to form a reaction product comprising a polyamide and a solvent;
[0026] heating the reaction product under a temperature and time sufficient to remove water and form polyimide particles;
[0027] filtering and washing the formed polyimide particles;
[0028] drying the washed polyimide particles to form a polyimide composition, wherein the polyimide composition comprises the polyimide particles;
[0029] wherein when the polyimide composition consists of particles of a polyimide polymer, the polyimide composition has an apparent density of < 0.25 grams per cubic centimeter.
[0030] (i) ODA, (ii) PMDA, (iii) PPD, (iv) BPDA, and (v) solvent are combined for a time and under conditions sufficient to form a reaction product comprising a polyamide and solvent. As used herein, "polyamide" includes polyamic acid. The monomers can be combined using methods known in the art.
[0031] The temperature at which the monomers (i) - (iv) and solvent are combined is a temperature sufficient to cause a reaction, alternatively from room temperature to an elevated temperature, alternatively room temperature, alternatively from room temperature to 120 degrees Celsius, alternatively an elevated temperature to 90 degrees Celsius, alternatively from 50 to 80 degrees Celsius.
[0032] The polyamide reaction product is subjected to conditions sufficient, alternatively heated, alternatively heated at a temperature from 70 °C to 190 °C, alternatively 110 °C to 170 °C, alternatively 110 °C to 150 °C, to convert the polyamide to an insoluble polyimide and remove water. The heating can be performed in a high pressure vessel, such as a Parr reactor, at an elevated pressure. Those skilled in the art will know how to heat the polyamide in a solvent to convert to a polyimide.
[0033] The combining and heating steps can be performed in the same or different vessels, alternatively in separate vessels.
[0034] The polyimide particles are filtered and washed. The polyimide is filtered using methods known in the art. For example, the polyimide and solvent can be passed through a Buchner funnel to recover the polyimide. Those skilled in the art will know how to filter the polyimide. The polyimide is washed with solvent and dried. Those skilled in the art will know how to wash and dry the polyimide. The polyimide is dried at a temperature from 100 °C to 230 °C, alternatively 140 °C to 190 °C, alternatively about 180 °C, to convert the polyimide slurry to a polyimide resin in the form of a powder (or particles). The filtering and washing are typically performed in separate vessels compared to the combining and reaction steps.
[0035] When the polyimide composition consists of particles of polyimide polymer, as described above, the polyimide composition has an apparent density of < 0.25 grams per cubic centimeter.
[0036] The method of making the polyimide composition can further include combining a filler with the reaction product prior to or during the heating step. The filler is as described herein. The filler can change the apparent density of the polyimide particles. The apparent density is relative to the unfilled composition and unfilled polyimide particles.
[0037] In one embodiment, the polyimide can be derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, for example, using a solution imidization process according to the following. Typically, the diamines (PPD and ODA) are first dissolved in a solvent to form a diamine component. Typically, after the diamine component is dissolved in the solvent at the desired concentration, the dianhydrides (BPDA and PMDA) are added to the reaction solution in substantially equimolar amounts to form a polyamic acid (PAA) polymer solution. In one embodiment, it is possible for the polyimide polymer to have a slight molar excess of either the dianhydride or diamine component, alternatively a molar excess of 0.5% to 1.0% of the diamine component, which has been found to provide good results. In another embodiment, a stoichiometry close to equimolar diamine and dianhydride is used. The resulting PAA polymer solution is transferred over a period of time to a heated solution of solvent. The transferred PAA polymer solution is continuously heated and stirred, causing the soluble PAA to react to form an insoluble polyimide slurry. The resulting polyimide slurry is washed with solvent and dried at 100°C to 230°C, alternatively 110°C to 190°C, alternatively 110°C-150°C, to convert the polyimide slurry to a polyimide resin in the form of a powder or granules having a high surface area. Optimum temperatures result in higher process efficiency and better physical properties of the polyimide granules or parts made from the polyimide granules, such as apparent density.
[0038] Solvents include, but are not limited to, organic solvents whose functional groups will not react to any appreciable extent with either of the reactants (anhydride or diamine). The solvent can exhibit a pH of about 8 to 10, which can be measured by mixing the solvent with a small amount of water and then measuring with pH paper or a probe. Such solvents include, for example, pyridine. Other solvents can also be used, which do not necessarily have a pH between 8 and 10, and additives such as B-methylpyridine can be added to change the pH of the solvent. Examples of solvents that can be used include, but are not limited to, dimethylacetamide (DMAC), n-methyl-2-pyrrolidone (NMP), dimethylsulfoxide (DMSO), and B-methylpyridine, and mixtures thereof. Of the solvents disclosed in Galland U.S. Patent No. 3,179,614 to Edwards, pyridine (K = 1.4 x 10 ) is the preferred solvent for these reactants in the polymerization reaction, as well as being used as a catalyst. In order for the dianhydride and diamine to react to form a PAA polymer solution, a basic catalyst is required. Since pyridine is a basic compound, it serves as both a catalyst and a solvent.
[0039] The amount of solvent is important to obtain a product with the desired particle size, low apparent density, and high surface area. In particular, the solvent should be present in an amount such that the concentration of the PAA polymer solution is about 1 to 15 weight percent solids, preferably about 5 to 12 weight percent solids. Those skilled in the art will be familiar with methods of making polyimide compositions and how to select the appropriate amount of solvent.
[0040] In one embodiment, the toughness of a part made from a polyimide composition is greater than a part made from a mixture of polymers A) and B), where polymer A) is derived from ODA and PMDA monomers and polymer B) is derived from PPD and BPDA monomers, alternatively B) is derived from PPD, MPD, and BPDA, and where the molar ratio of ODA, PMDA, PPD, and BPDA in the polyimide is the same as in the mixture of polymer A) and polymer B).
[0041] Polymer A) is derived from ODA and PMDA monomers, where the molar ratio of ODA and PMDA in polymer A) is the same as in a polyimide derived from ODA, PMDA, PPD, and BPDA used to make the part. Polymer B) is derived from PPD and BPDA monomers, alternatively B) is derived from PPD, MPD, and BPDA, where the molar ratio of PPD and BPDA monomers is the same as in a polyimide derived from ODA, PMDA, PPD, and BPDA used to make the part.
[0042] Examples of polymer A) include polymers made with a molar ratio of ODA to PMDA of about 45 : 55 to 55 : 45, alternatively about 50 : 50. Examples of polymer B) include polymers made with a molar ratio of PPD to BPDA of about 45 : 55 to 55 : 45, alternatively about 50 : 50.
[0043] Polymer A) and polymer B) are made according to the methods described and exemplified herein for making polyimide compositions. To make a part from polymer A) and B), a physical mixture of particles of polymer A) and B) is made by mixing with typical mixing equipment used to make polyimide particles. The physical mixture is then shaped into a part by molding the mixture under conditions sufficient to form a part, alternatively under elevated pressure and ambient temperature as described below with respect to polyimide compositions, alternatively at a pressure of about 20,000 to 100,000 psi (345 to 690 MPa), or preferably 50,000 to 100,000 psi at ambient temperature.
[0044] A polyimide composition comprising: a polyimide derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein a part made from the polyimide composition has a specific gravity greater than a mixture of polymer A) and polymer B), wherein polymer A) is derived from ODA and PMD monomers, and polymer B) is derived from PPD and BPDA monomers, and wherein the molar ratio of ODA, PMDA, PPD, and BPDA in the polyimide is the same as in the mixture of polymer A) and polymer B).
[0045] The monomers ODA, PMDA, PPD, BPDA, polymers A) and B), and the ODA molar fraction of ODA, PMDA, PPD, and BPDA are as described above.
[0046] Specific gravity is known in the art. One skilled in the art will understand how to measure and calculate the specific gravity of a part. In one embodiment, the specific gravity is greater than 0.138 g / cm 3 , 0.138 g / cm 3 to 1.54 g / cm 3 .
[0047] Specific gravity refers to the specific gravity of a part made from the polyimide composition without the addition of other additives such as fillers. Fillers and other additives can change the specific gravity; however, a part made from a filled polyimide composition will have a specific gravity greater than a part made from a mixture of polymers A and B. When fillers are included in the polyimide composition, the specific gravity of the part refers to the specific gravity of a part formed from a polyimide composition derived from the same monomer ratio and using the same method and conditions but without the addition of any fillers.
[0048] Specific gravity can be measured according to methods known in the art. One skilled in the art will understand how to measure specific gravity. The specific gravity of a part is calculated by the following equation herein:
[0049] .
[0050] A polyimide composition comprising:
[0051] a polyimide derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein the sum of the molar fraction of BPDA and PMDA is about 1 and the sum of the molar fraction of PPD and ODA is about 1, and wherein the relationship of the molar fraction of BPDA based on dianhydride to the molar fraction of PPD based on diamine is PPD - 0.2 < BPDA, 0.05 < BPDA < 0.95, and 0.05 < PPD < 0.95.
[0052] In one embodiment, the sum of the mole fraction of BPDA and PMDA in the polyamide is about 1 and the sum of the mole fraction of PPD and ODA is about 1 and alternatively the relationship between the mole fraction of BPDA based on dianhydrides and the mole fraction of PPD based on diamines is PPD - 0.2 < BPDA, 0.05 < BPDA < 0.95, and 0.05 < PPD < 0.95. The mole fraction of BPDA is based on total dianhydrides and the mole fraction of PPD is based on total diamines.
[0053] In one embodiment, the mol% of BPDA relative to other monomers combined to make the polyimide particles is > (the mol% of PPD + 0.2). This mol% of BPDA will result in a part having sufficient toughness.
[0054] One skilled in the art will know how to calculate the mol% and mole fraction of monomers that fall within the ranges described and to vary the manufacturing process described above to produce polyimides having the monomer fraction and mol%.
[0055] In one embodiment, the part made from the polyimide composition has a toughness greater than 0.80 Ksi, alternatively greater than 0.85 Ksi, alternatively 0.80 KSI to 5 Ksi, alternatively 0.80 Ksi to 1.5 Ksi, alternatively 0.85 Ksi to 1.0 Ksi.
[0056] Toughness refers to the toughness of a part made from the polyimide particles without the addition of other additives such as fillers. Fillers and other additives can affect toughness. Thus, when fillers are included in the polyimide composition, the toughness of a part as used herein refers to the toughness of a part formed from a polyimide composition derived from the same monomer ratios and using the same methods and conditions but without the addition of any fillers.
[0057] ODA, PMDA, PPD, BPDA, the part made from the polyimide composition, and how to determine the toughness of the part are described above. One skilled in the art will know how to determine the toughness of a part derived from the monomers listed in the above description.
[0058] A polyimide composition comprising:
[0059] A polyimide derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers and comprising one or more of the following repeat units
[0060] 、
[0061] 、
[0062] 、
[0063] and
[0064] .
[0065] The surface area of the polyimide in the polyimide composition of the present invention is typically at least 20 m 2 / g. Preferably the surface area is at least 75 m 2 / g to achieve acceptable physical properties and ease of processability.
[0066] The average molecular weight (Mw) of the polyimide as measured by GPC is greater than 50,000, preferably greater than 100,000, alternatively greater than 150,000 g / mol. Those skilled in the art will know how to determine the molecular weight and how to control the molecular weight during production of the polyimide.
[0067] In one embodiment, the polyimide composition further comprises a filler. Examples of fillers include, but are not limited to, carbon-containing fillers such as graphite and carbon fibers, and inorganic fillers such as kaolin, molybdenum sulfide, tungsten sulfide, and boron nitride, and polymeric fillers such as polymers and copolymers of tetrafluoroethylene to improve wear and friction properties while maintaining the excellent mechanical properties and oxidative stability of the polyimide. In addition to improving friction and wear properties, fillers can be added to affect other properties of the polymer, for example, but not limited to, increasing the stiffness or hardness of the polymer and parts derived therefrom. The fillers can be present in amounts ranging from 0.1 to 80 wt.%. The particular filler or fillers selected and the amount used will of course depend on the desired effect in the final composition, which will be apparent to those skilled in the art. These fillers are typically incorporated into the heated solvent prior to transferring the PAA polymer solution, such that the polyimide precipitates in the presence of the fillers incorporated thereby. The form of the fillers will depend on the function of the fillers in the final product. For example, the fillers can be in the form of microparticles or fibers.
[0068] After the addition of the fillers, the apparent density can be higher than 0.25 g / cm 3 .
[0069] A part comprising the polyimide composition described above, wherein the part has a toughness of > 0.80 Ksi, a specific gravity of > 1.38 g / cm 3 , or a toughness of > 0.80 Ksi and a specific gravity of > 1.4 g / cm 3 . The toughness and specific gravity are as described above.
[0070] The polyimide composition can be molded under elevated pressure into a wide variety of configurations to form a part, alternatively, a part can be cold press molded to form a green part, which is then heated to a temperature above 400°C, alternatively, a part can be manufactured by hot pressing the polyimide composition, wherein both high pressure and high temperature are applied simultaneously. It has been found that it is particularly convenient to mold the polyimide composition at a pressure of about 50,000 to 100,000 psi (345 to 690 MPa) at ambient temperature. Lower pressures can also be used, but this can increase the porosity of the final part and can also compromise the strength of the part. Those skilled in the art will know how to manufacture molded parts from the polyimide composition of the present invention and the polyimide composition manufactured by the method of the present invention.
[0071] A part manufactured from the polyimide composition of the present invention and further comprising a filler has at least 50%, alternatively 75%, alternatively 100% less wear than a part manufactured from a mixture of polymers A and B having the same monomer composition and filler as the polyimide composition described above. Wear is determined according to the procedure described in the Examples section.
[0072] The present invention can include the following aspects:
[0073] 1. A polyimide composition comprising: a polyimide derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein the polyimide has an apparent density of < 0.25 grams per cubic centimeter.
[0074] 2. The polyimide composition of aspect 1, wherein a part manufactured from the polyimide composition has a toughness greater than 0.80 Ksi and a specific gravity of < 1.4 g / cm 3 .
[0075] 3. A polyimide composition comprising: a polyimide derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein the polyimide has a specific gravity greater than a mixture of polymer A) and polymer B), wherein polymer A) is derived from ODA and PMD monomers and polymer B) is derived from PPD and BPDA copolymer, and wherein the mole fraction of ODA, PMDA, PPD, and BPDA in the polyimide is the same as in the mixture of polymer A) and polymer B).
[0076] 4. The polyimide composition of aspect 3, wherein a part manufactured from the polyimide composition has a specific gravity greater than 1.4 g / cm 3 .
[0077] 5. A polyimide composition comprising: a polyimide derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein the sum of the mole fraction of BPDA and PMDA is about 1 and the sum of the mole fraction of PPD and ODA is about 1, and wherein the relationship of the mole fraction of BPDA to the mole fraction of PPD is PPD - 0.2 < BPDA, 0.05 < BPDA < 0.95, and 0.05 < PPD < 0.95.
[0078] 6. A polyimide composition comprising: a polyimide derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers and comprising one or more of the following repeat units
[0079] ,
[0080] ,
[0081] ,
[0082] and
[0083] .
[0084] 7. A polyimide composition comprising: a polyimide derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein a part made from the polyimide composition has a toughness greater than 0.80 Ksi.
[0085] 8. A polyimide composition comprising: a polyimide derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers, wherein a part made from the polyimide composition has a specific gravity greater than 1.4 g / cm 3 .
[0086] 9. The polyimide composition of any of the preceding aspects, further comprising a filler.
[0087] 10. The polyimide composition of any of the preceding aspects, wherein the mole ratio of diamine monomers to anhydride monomers is about 1.
[0088] 11. A part comprising: the polyimide composition of any of aspects 1 to 10.
[0089] 12. The part of aspect 11, wherein the part is molded.
[0090] 13. The part according to aspect 10 or 11, wherein the part is a clutch roller.
[0091] 14. A method of making a polyimide composition comprising: combining (i) ODA, (ii) PMDA, (iii) PPD, (iv) BPDA, and (v) a solvent under time and conditions sufficient to form a reaction product mixture comprising a polyamide and solvent; heating the reaction mixture at a temperature > 110 °C and for a time sufficient to form polyimide particles and remove water; filtering and washing the solid polyimide particles; and drying the solid polyimide particles to form a polyimide composition comprising the solid polyimide particles, wherein the temperature to which the reaction mixture is heated is selected to result in solid polyimide particles having an apparent density of less than 0.25 g / cm3. 3
[0092] 15. The method according to aspect 14, further comprising combining the dried polyimide with a filler.
[0093] 16. The method according to aspect 14 or 15, further comprising the step of sintering and molding the dried polyamide or dried polyimide and filler to form the part.
[0094] 17. The method according to aspect 16, wherein the part has a toughness greater than 0.80 Ksi.
[0095] 18. The method according to one of aspects 16 or 17, wherein the part has a specific gravity greater than a part made from a mixture of polymer A) and polymer B), wherein polymer A) is derived from ODA and PMD monomers and polymer B) is derived from PPD and BPDA, and wherein the molar composition of ODA, PMDA, PPD, and BPDA in the polyimide is the same as in the mixture of polymer A) and polymer B).
[0096] 19. The method according to any one of aspects 16-18, wherein the part has a specific gravity greater than 1.4 g / cm3. 3
[0097] 20. The method according to any one of aspects 14-19, wherein the relationship of the mole fraction of BPDA to the mole fraction of PPD is PPD - 0.2 < BPDA < PPD + 0.2, 0.05 < BPDA < 0.95, and 0.05 < PPD < 0.95.
[0098] 21. A part made according to the method of any one of aspects 16-20.
[0099] 22. The part according to aspect 21, wherein the part is a clutch roller, a seal ring, a spherical washer, a compressor seal, a lip seal, a valve seat, a ball bearing retainer, and a drive disc.
[0100] 23. The part according to aspect 21, wherein the part further comprising a filler made from the polyimide composition has at least 50% less wear compared to a part made from a homopolymer of A and B having the same monomer composition and filler.
[0101] The polyimide composition of the present invention forms parts having increased toughness and specific gravity. The polyimide composition can be used to make parts for clutch rollers and the like applications used in powered sports vehicles. Examples
[0102] The following examples are included to demonstrate preferred embodiments of the application, but should not be deemed to limit the application, which is described in the claims below. It should be understood by those skilled in the art that the techniques disclosed in the following examples represent techniques discovered by the inventors to function well in the practice of the application, and, accordingly, can be considered to constitute preferred modes for its practice. However, it should be appreciated that those skilled in the art can readily make many changes to the techniques without departing from the spirit and scope of the application as known from this disclosure. Unless otherwise indicated, all percentages are by weight %. The following table describes the abbreviations used in the examples.
[0103] Table 1. List of abbreviations used in the examples.
[0104]
[0105] In the following Examples 1-24 and Comparative Examples 1-2 and 7-13, copolymeric polyimide compositions were prepared using a solution imidization process in which a mixture of diamines derived from p-phenylenediamine (PPD) and 4,4’ oxydianiline (ODA) was reacted with a mixture of dianhydrides derived from 3,3’,4,4’-biphenyltetracarboxylic dianhydride (BPDA) and pyromellitic dianhydride (PMDA) in amounts indicated in the examples using a procedure generally similar to the procedures outlined in U.S. Patent No. 3,179,631 to Gall, U.S. Patent No. 3,249,588 to Endrey, and U.S. Patent No. 5,886,129 to Delcolibus, all of which are hereby incorporated by reference as their descriptions relate to the preparation of copolymeric polyimide compositions. To illustrate the present invention, both polymerization and imidization were carried out with pyridine as the solvent.
[0106] Polymerization to form polyamic acid (PAA) was performed in a Chem Glass round bottom 500 ml glass jacketed reaction kettle with the bottom removed to drain the final polyamic acid solution. The reaction vessel was agitated by a Cole-Palmer Servo Dyne Model 50008 overhead stirrer with a marine impeller. Temperature within the reaction kettle was controlled by a circulating heat transfer fluid from a Huber Ministat cc3 recirculating heater chiller. The circulator used a silicone based heat transfer fluid that was stable up to 150 °C.
[0107] Typical theoretical batch sizes for polymerization included about 60 g of polymer in anhydrous pyridine. Unless otherwise noted, polymerization was performed in pyridine solvent at a concentration or solid loading of 10 wt%. The reported solid concentrations were based on the weight of the polyamic acid (PAA) polymer, not the weight of the final imidized polymer. In preparation for a polymerization run, the target copolymer composition (defined by the mole fraction of monomers), polymer concentration, and monomer imbalance % were fixed. Monomer imbalance was defined by the following equation:
[0108]
[0109] For all illustrative examples presented herein, polymerization was performed in a diamine rich environment with a monomer imbalance of around 0.75%.
[0110] Molecular weight of polyamic acid (PAA) solutions was measured using an Agilent GPC instrument, which included an Agilent 1290 UHPLC assembly, binary delivery pump, autosampler, separation column compartment, and UV detector. The GPC was equipped with two stationary phases, consisting of two Agilent PLgel 5 pm MIXED-C 300 mm x 7.5 mm columns and one PLgel 5 pm Guard column 50 mm x 7.5 mm. The instrument was controlled by Chemstation OpenLabs software with Cirrus GPC add-on. The columns were calibrated using polystyrene polymer standards (Easi Cal PS-1) sold by Agilent.
[0111] The mobile phase for the GPC was prepared by pre-mixing 98.436% dimethylacetamide (DMAC), 0.357% orthophosphoric acid, 0.942% tetrahydrofuran (THF) (unstabilized), and 0.265% lithium bromide (LiBr). All percentages are by weight. The sample injection volume was fixed at 2 μΐ. The flow rate of the mobile phase was set to 0.5 ml / min. Elution was isocratic. The stop time for the GPC was 55 minutes. The GPC used a UV detector, which was set to detect at 268 nm.
[0112] Imidization of the polyamic acid was performed in a 1000 ml Parr high pressure reactor with an anchor impeller. The PAA solution was transferred to the high pressure Parr vessel using a Teledyne ISCO 500 D pump. The PAA solution in the ISCO pump was heated to 70 °C before being transferred to the high pressure reactor. The Parr vessel was capable of being heated to 200 °C by a resistance heater. The imidization temperature in the Parr reactor was varied in the range of 110 °C to 175 °C during the PAA transfer and during the imidization.
[0113] After imidization, a small sample of the slurry was collected for particle size distribution analysis. The PSD of the polyimide wet slurry was determined using a Malvern Panalytical Mastersizer 3000 laser light scattering instrument. The laser light scattering measurements were performed in deionized water. All measurements were performed at room temperature and no ultrasonic energy was used during the measurements.
[0114] The remaining portion of the polyimide slurry was transferred to a Buchner funnel for filtration and washing of the co-polymeric polyimide microparticles. The filtration rate was controlled to manage the drainage of the pyridine solvent and prevent premature crack formation in the filter cake. Just before all of the pyridine was drained from the filter cake, four volumes of clean acetone were added to the filter cake to perform a displacement wash of the filter cake. After all of the solvent was drained from the filter cake, the wet cake was left to air dry in a fume hood for about 1 hour before it was transferred to a vacuum oven at 175 °C to dry overnight.
[0115] The apparent density of the milled co-polymeric polyimide powder was measured using a volumetric method according to the test method described in ASTM-D1895-17, titled “Standard Test Methods for Apparent Density, Bulk Factor, and Interstitial Porosity of Plastics Materials”.
[0116] The specific surface area of a dry co-polymeric polyimide powder sample was measured using the BET method described by S. Brunauer, P. H. Emmett, and E. Teller in the Journal of American Chemical Society, Volume 60, 309 (1938). The sample was degassed at < 100 µm Hg at 120 °C for 12 hours before testing. Nitrogen adsorption / desorption measurements were performed on a Micromeritics ASAP 2420 type porosimeter at 77.3 K. The surface area measurements utilized five-point adsorption isotherms collected in the range of 0.05 to 0.20 P / P0 and were analyzed using the BET method.
[0117] To perform tensile testing, the copolymerized polyimide powder resin was compression molded at an applied pressure of 100,000 psi to form green tensile bars. The form and dimensions of the tensile bars are described in ASTM E8 test method, entitled "Standard Tension Test Specimen for Powdered Metal Products - Flat Unmachined Tensile Test Bar." The molded green bars were sintered in a nitrogen atmosphere using a series of temperature ramps to slowly heat the part from room temperature to 405 °C over a 70 hour period and then held at 405 °C for 30 minutes and then the part was slowly cooled to room temperature. The long sintering cycle (70 hours) is not a prerequisite to demonstrate the high toughness properties of the copolymerized polyimide resin. A shorter sintering cycle can also be used if no bubbles or voids are formed in the part in a faster sintering cycle. A longer sintering time can also be used depending on the size of the part being sintered.
[0118] The mechanical properties of the copolymer resin were obtained by testing the tensile bars at room temperature on a 30 KN Instron testing machine. The tensile bars were subjected to a strain rate of 5 mm / min. Tensile measurements were made on at least 5 bars and the tensile properties reported are the average of the tests on at least 5 bars. The toughness of the sample was estimated by calculating the area under the stress strain curve using numerical integration and the average of the 5 bars was reported.
[0119] The copolymer resin powder samples were also compression molded to form cylindrical green pellets 8 mm in diameter and 8 mm in height which were then sintered at 405 °C using a 70 hour sintering cycle. The compression properties of the cylindrical parts were measured on a 29 kip MTS test machine frame equipped with a 100 KN load cell and laser extensometer to measure the deformation of the part under stress. The compression speed for all tests was fixed at 2.4 mm / min, which corresponds to a compression strain rate of 0.005 seconds -1 As with the tensile properties, the compression properties were reported as the average obtained after testing 5 cylindrical samples.
[0120] The specific gravity of the parts was measured by the water immersion method. The parts were weighed in air and then weighed when fully immersed in a 0.05 wt.% soap solution. The soap solution is necessary to ensure that no tiny air bubbles are adhered to the test sample. The specific gravity of the part was calculated by the following equation
[0121] .
[0122] The glass transition temperature (Tg) of the copolymerized polyimide polymer was measured by differential scanning calorimetry (DSC) using a TA Instruments Q2000 DSC. The sample was heated at a rate of 10 °C / min from room temperature to 300 °C and then cooled at a rate of 10 °C / min to -30 °C. The sample was then heated at a rate of 10 °C / min from -30 °C to 300 °C. The glass transition temperature was determined from the second heat curve.g ) was obtained by testing rectangular sintered bars on a dynamic mechanical analyzer (TA Instruments Q800 DMA). The sample bar was clamped on a dual cantilever and deformed at the center at a strain amplitude of 0.25% and a frequency of 1 Hz. The temperature sweep used for the test was from 40 °C to 425 °C at a rate of 2 C / min. The temperature corresponding to the peak of the tan delta curve was reported as Tg. g .
[0123] Friction and wear testing of the unfilled and filled copolymers of the present invention was tested on a Falex Block-on-Ring Tester manufactured by Falex Corporation of Sugar Grove, IL. ASTM test methods D 2714-94 and G77-17 describe the calibration and operation of the Falex Block-on-Ring Tester and its use in evaluating the friction and wear characteristics of materials. The simplest form of the machine consists of a rotating metal ring (also called the counter surface) and a stationary test block loaded against the rotating ring. The test block is machined from a test sample disc whose wear and friction characteristics are to be evaluated. After machining, the test block fits snugly against the outer surface of the counter surface metal ring. During testing, the inner curved surface of the test piece with an area of 0.1608 in 2 is always in contact with the outer surface of the ring, and the pressure exerted on the block is constant throughout the test. The machined test block represents a section of bushing, ¼” (6.35 mm) in thickness, connected to the sample holder by a hemispherical ball to align the machined test block with the ring as shown in Figure 1 The load is applied to the block by dead weight through a lever arm that is magnified by a factor of thirty. Thus, 1 lb. of dead weight magnifies the force on the block to 30 lbs. The metal ring used in all tests is a standard “alpha” ring machined from SAE 4620 steel with a surface roughness of Rc 58 - 63 and 6 – 12 rms. A new ring is used for each block-on-ring test. The sample holder is connected to a load cell that measures the frictional force between the block and the ring and provides an output in pounds force.
[0124] Test samples were prepared by compression molding polyimide powder into discs that were 1” in diameter and approximately 6 mm in thickness. All sample discs were molded at 80,000 psi. Each green disc was sintered using the same temperature and sintering cycle as used for the tensile bars described previously. After sintering, each disc was machined to form a Figure 1The curved blocks were shown. After machining to conform to the standard configuration, the test blocks were cleaned with solvent to remove contaminants from the sample surface and then dried in a vacuum oven at 150°C. Each test block was weighed to the nearest 0.1 mg. Similarly, the steel ring to be used in the test was cleaned with solvent to remove the rust inhibitor coating from the surface, dried and then weighed before mounting on the Falex instrument.
[0125] Friction and wear testing on the Falex instrument was conducted in two different modes. In the constant pressure-velocity (PV) test mode, a fixed load was applied to the test block and the ring rotated at the same pre-set constant velocity throughout the duration of the test. For the purpose of testing the copolymers of the present invention, the test duration for the constant PV test was 24 hours. In the pressure velocity (PV) limit test, the load and / or velocity was increased every 20 minutes based on the set program shown in Table 2 until there was a significant increase in temperature and / or friction. The point of stopping for the PV limit test became apparent when the temperature and friction rose exponentially, and at this point the instrument was turned off, terminating the test. The PV conditions just prior to the end of the test were the PV limit for the tested material.
[0126] Table 2.
[0127]
[0128] For both test modes, the procedure for preparing the samples was the same. After the test sample (block) was weighed and the thickness measured, the test block was mounted on the instrument with the self-aligning test specimen holder. The opposing surface ring was then placed on the machine spindle. Based on the pressure value (P) required during the test, a known weight was placed on the machine weight pack. Next, the desired velocity (V) was set to achieve the desired PV conditions. The constant PV test was run for a total of 24 hours, including a 1.5 hour "run-in" period to achieve full seating of the block and ring. During the test, the Falex instrument periodically monitored and reported the coefficient of friction between the surface of the test block and the opposing surface of the ring. After the completion of the constant PV test, the test block was thoroughly dried at 150°C for 24 hours and its weight was measured to the nearest 0.1 mg. The weight loss of the block was utilized to calculate the wear loss on a weight basis. The new thickness of the block was then measured to determine an alternate measure of wear based on dimensional change. The wear based on weight loss was reported as K w . The wear rate (inches per hour) and the wear factor based on thickness change - K t .
[0129] Example 1
[0130] A polyimide obtained from 40 mol % BPDA, 40 mol % PPD, 60 mol % PMDA, and 60 mol % ODA, where the mol % of the dianhydride components is stated on a total dianhydride basis and the mol % of the diamines is on a total diamine basis.
[0131] Anhydrous pyridine was obtained by drying the solvent over molecular sieves. Both dianhydrides were stored in a vacuum oven at 150 °C for at least 12 hours prior to the start of the experiment. 7.025 g of PPD and 19.512 g of ODA were weighed out and set aside. Similarly, 18.970 g of previously dried BPDA and 21.095 g of previously dried PMDA were weighed out and set aside.
[0132] 562 g of anhydrous pyridine, which had been dried over molecular sieves, was added to a 500 cc jacketed reactor from Chemglass®. The reactor's jacket temperature was set to 45 °C and the stirrer speed was set to 125 rpm. When the temperature of the solvent reached 35 °C, both diamines were added to the reactor. The temperature in the reactor was then raised to 50 °C. When all of the diamines were visibly dissolved in the pyridine tail, both dianhydrides were added to the kettle simultaneously, and the balance of the 62.4 g of anhydrous pyridine set aside for this purpose was used to rinse any remaining dianhydrides from the weighing pan. After the addition of the dianhydrides was complete, the temperature on the jacket side was raised to 70 °C. The stirrer speed was also raised to 250 rpm at this time.
[0133] The exotherm generated by the heat of reaction between the diamines and the dianhydrides caused the temperature in the reactor to quickly rise to a maximum of 70 °C and then eventually stabilize. The polymerization reaction was allowed to continue for a total of 1 hour. At the end of the polymerization time, the stirrer was slowed and the viscous PAA solution that had formed was drained from the bottom take-off valve. A small amount of the polymer solution was set aside for the measurement of molecular weight. The number average molecular weight (M n ) and weight average molecular weight (M w ) of the PAA sample were measured to be 100,546 and 226,557 Daltons, respectively.
[0134] The imidization process was carried out in fed batch mode. At the start of the imidization process, approximately 100 ml of pyridine was initially added as a tail feed to the Parr vessel and heated to 114 °C. The anchor impeller was also started and set to a predetermined value. The agitator RPM was set to 200. Then 597.2 g of the polyamide acid solution discharged from the polymerization kettle was transferred to the bucket of the ISCO pump. The exact weight of the PAA solution transferred to the pump was recorded. Based on this value, the exact amount of pyridine tail feed required during the imidization process was calculated to be 166.7 g. Based on this calculation, 66.7 g of make-up pyridine was injected into the Parr reactor to get the correct amount of pyridine tail feed of 166.7 g. The ISCO pump was sealed and connected to the Parr reactor using stainless steel tubing and compression fittings. The PAA solution was transferred to the Parr reactor at a constant rate such that the entire solution transfer was completed in 90 minutes. At the end of the transfer, the internal temperature of the reactor was increased to 145 °C in 75 minutes. After reaching 145 °C, the contents of the vessel were held at this temperature for 30 minutes after which the reactor was cooled to room temperature.
[0135] The D50 of the polyimide particles in the slurry was measured to be 68.1 pm.
[0136] The remaining polyimide slurry was filtered and the resulting filter cake was washed with acetone and then dried under vacuum at 175 °C. The dried polyimide polymer was ground in a laboratory Wiley mill while being sieved through a 30 mesh screen.
[0137] The dried polymer was ground and characterized for apparent density (AD) and specific surface area (SA). The AD and SA of the copolymeric polyimide polymer were 0.159 and 112.4 m 2 / g, respectively.
[0138] The copolymer resin was compression molded into tensile bars and cylindrical pellets to measure compression properties. The green parts were sintered at 405 °C. The specific gravity of the sintered parts was 1.420. The T g from the tan delta curve was 371.4 °C.
[0139] The average tensile strength and % elongation of the 5 tensile bars measured were 18388 psi and 14.7%, respectively. The average toughness of the copolymeric polyimide resin was obtained from the stress strain curve to be 2.27 Ksi. The average compression strength measured was 750 MPa and the average breakage strain was 62.5%.
[0140] Example 2 - 8
[0141] Higher specific gravity, low apparent density, and higher toughness polyimide compositions containing BPDA, PMDA, PPD, and ODA. In these examples, the mol % of BPDA based on total dianhydride remains the same as the mol % of PPD based on total diamine.
[0142] The copolymeric polyimide resin compositions shown in Examples 2 - 8 were synthesized using the same method outlined in Example 1. Table 3 shows the polymer composition, the amount of each monomer used, and the solvent used during polymerization for Examples 2 - 8. Table 4 shows the conditions used for the imidization step to synthesize the copolymeric polyimide polymers of the invention and the properties of the polymer powder obtained after drying. Table 5 shows the properties of the polymer parts after sintering.
[0143] Table 3
[0144]
[0145] Table 4
[0146]
[0147] Table 5
[0148]
[0149] Comparative Examples 1 - 2
[0150] Homopolymers derived from BPDA and PPD and PMDA and ODA, respectively, exhibit worse toughness than the polyimides of the invention exemplified by Examples 1 - 8.
[0151] An imidized homopolymer of BPDA and PPD was obtained by polymerization and imidization reactions in a very similar manner as described in Example 1, except that the homopolymerization and subsequent imidization of BPDA-PPD was carried out with a ratio of pyridine to NMP of 10: 1 by weight. Since the polyamic acid homopolymer of BPDA and PPD is not miscible in pyridine, the solvent needs to be modified and a small amount of NMP is needed to ensure that the polyamic acid stays in solution. 18.776 g of PPD was dissolved in 624 g of pyridine-NMP mixture before the polymerization was started and then reacted with 50.574 g of BPDA at 50 °C. After the polymerization was completed, the transfer procedure in Example 1 was followed to slowly transfer 576 g of the resulting polyamic acid (PAA) homopolymer solution into 247 g of a 10: 1 mixture of pyridine and NMP. The temperature of the solvent was maintained at 114 °C during the PAA transfer. After the imidization of the polymer precipitated during this imidization process, the temperature of the reactor was increased to 145 °C to maximize the precipitation of the polymer and further increase the degree of imidization of the precipitated polymer. The D50 of the particle distribution was measured to be 76.6 pm. The polyimide solvent slurry was cooled to 60 °C and then filtered. The filter cake was washed with acetone and then dried in a vacuum oven at 180 °C as described in Example 1. The dried polymer was ground through a 30 mesh sieve and then further used. The AD of the powder was measured to be 0.170 g / cc. The polymer powder was compression molded to form test parts for tensile testing. The tenacity of the homopolymer under the action of tension was obtained from the stress-strain curve. The properties of the finished parts of the BPDA PPD homopolymer are shown in Table 6. The BPDA-PPD homopolymer exhibited very low elongation and very low tenacity.
[0152] Table 6
[0153]
[0154] An imidized homopolymer of PMDA and ODA was obtained by polymerizing 30.537 g PMDA with 28.132 g ODA in 362 g of pure pyridine solvent. A solution-formed PAA homopolymer was imidized by slowly transferring 290 g of the solution-formed PAA homopolymer at 114 °C into 86 g of pyridine, after which the entire solution was heated to 145 °C to precipitate and form a PMDA-ODA polyimide homopolymer. The homopolymer was filtered, washed, and vacuum dried as described in Example 1. The dried polymer was ground. The AD was measured to be 0.177 g / cc. The polymer powder was compression molded to form test parts for two tensile tests. The tenacity of the homopolymer under tensile action was obtained from the stress-strain curve. The properties of the finished parts of the homopolymer PMDA ODA are shown in Table 7. The PMDA-ODA homopolymer exhibited higher elongation and higher tenacity than the BPDA-PPD homopolymer, but still exhibited much lower tenacity than the copolymers shown in Examples 1 - 8.
[0155] Table 7
[0156]
[0157] Comparative Example 3 - 6
[0158] Polyimide blends were produced by blending polymers of BPDA and PPD with polymers of PMDA and ODA in different weight ratios to compare the properties of the blended polymer compositions with those of polyimide compositions containing similar amounts but of BPDA, PMDA, PPD, and ODA in the polymer backbone. The blended polymers in these examples showed inferior strength, elongation, and tenacity compared to the copolymeric polyimide compositions with the same monomer composition.
[0159] An imidized homopolymer of BPDA-PPD was synthesized in exactly the same way as described in Comparative Example 1. After the imidization step was complete, the polymer slurry in pyridine-NMP mixture was left over for further processing in subsequent examples.
[0160] An imidized homopolymer of PMDA and ODA was manufactured by E. I. duPont & Nemours company and finished parts and shapes made from this polymer were sold under the trade name Vespel® SP-01. A sample of SP-01 polyimide slurry was collected from the Vespel® manufacturing plant and further processed in subsequent examples. The D50 of the SP-01 slurry was measured to be 27.0 µm.
[0161] Comparative Example 3
[0162] A BPDA-PPD homopolymer slurry containing 10 g of solid BPDA-PPD homopolymer and a PMDA-ODA homopolymer slurry containing 40 g of PMDA-ODA were weighed into a round bottom flask and mixed vigorously with an overhead stirrer assembly for 15 minutes. The blended polymer slurry was filtered and the wet cake was washed with excess acetone. The acetone containing cake was dried in a vacuum oven at 180 °C for 16 hours and the dried polymer was ground through a 30 mesh screen. Because the resulting polymer blend was obtained by mixing the two homopolymer components in slurry form, it is reasonable to assume that the individual particles making up the two homopolymer slurries were intimately dispersed, resulting in a well-mixed polymer system. In the resulting polymer blend, BPDA should be 20% by mol % based on total dianhydride and PPD should be 20% by mol % based on total diamine. The blended polymer powder was compression molded into a tensile bar, sintered, and tested for properties in the same manner as described in Example 1.
[0163] Comparative Example 4
[0164] A BPDA-PPD homopolymer slurry containing 20 g of solid BPDA-PPD homopolymer and a PMDA-ODA homopolymer slurry containing 30 g of PMDA-ODA homopolymer were blended together and the resulting slurry was processed to form a dry powder and a part was tested as described in Comparative Example 3.
[0165] Comparative Example 5
[0166] A BPDA-PPD homopolymer slurry containing 30 g of solid BPDA-PPD homopolymer and a PMDA-ODA homopolymer slurry containing 20 g of PMDA-ODA were blended together and the resulting slurry was processed to form a dry powder and a part was tested as described in Comparative Example 3.
[0167] Comparative Example 6
[0168] A BPDA-PPD homopolymer slurry containing 40 g of solid BPDA-PPD homopolymer and a PMDA-ODA homopolymer slurry containing 10 g of PMDA-ODA were blended together and the resulting slurry was processed to form a dry powder and a part was tested as described in Comparative Example 3.
[0169] Final properties of the blended polymer compositions of Comparative Examples 3-6 are shown in Table 8.
[0170] Table 8
[0171]
[0172] In Figure 2 , 3and 4, the results from Comparative Examples 3 - 6 are compared graphically with the results from Examples 1 - 8, where the tensile strength, % elongation at break, and tensile toughness of the copolymerized polyimides of the present invention are compared with the blended homopolymers when plotted against the BPDA and PPD content in the polymer. These examples and the resulting graphs show that the copolymerized polyimides of the present invention exhibit significantly better performance than the blended homopolymers with the same BPDA, PPD, PMDA, and ODA content.
[0173] Examples 9 - 17
[0174] Additional higher specific gravity, low apparent density, and higher toughness copolymerized polyimide compositions containing BPDA, PMDA, PPD, and ODA. In Examples 1 - 8 of the present invention, the mol% of BPDA and the mol% of PPD based on the total dianhydride and total diamine, respectively, were kept equal. In Examples 9 - 17, the mol% of BPDA was not equal to the mol% of PPD, but the tensile properties and toughness were similar to those observed in Examples 1 - 8, thus indicating that the content of BPDA and PPD in the copolymer does not have to be the same to produce a high toughness copolymer composition.
[0175] The copolymerized polyimide resin compositions shown in Examples 9 - 17 were synthesized using the same method outlined in Example 1, except that during the imidization of the PAA transfer, the temperature ranged between 110 °C and 150 °C. Table 9 shows the polymer composition of Examples 9 - 17, the amount of each monomer used, and the solvent used during polymerization. Table 10 shows the conditions used for the imidization step to synthesize the copolymerized polyimide polymers of the present invention and the properties of the polymer powder obtained after drying. Table 11 shows the properties of the polymer parts after sintering.
[0176] Table 9
[0177]
[0178] Table 10
[0179]
[0180] Table 11
[0181]
[0182] + The sample bar did not break under tension and the test ended before the test sample failed.
[0183] Comparative Examples 7 - 13
[0184] These examples show that when the mol % of BPDA based on total dianhydride content and the mol % of PPD based on total diamine content in the copolymer composition are significantly different, the copolymerized polyimide exhibits high AD, low specific gravity, and low toughness in the final sintered part.
[0185] The copolymerized polyimide resin compositions shown in Comparative Examples 7 - 13 were also synthesized using the same method outlined in Example 1. Table 12 shows the polymer composition used to synthesize the copolymerized polyimide polymers of the present invention, the amount of each monomer used, and the solvents used during the polymerization and imidization steps. Table 13 shows the conditions of the imidization step used to synthesize the copolymerized polyimide polymers of the present invention and the properties of the polymer powder obtained after drying. Table 14 shows the properties of the polymer parts after sintering.
[0186] Table 12
[0187]
[0188] Table 13
[0189]
[0190] Table 14
[0191]
[0192] All of the comparative examples presented herein exhibit significantly worse properties than the copolymers of the present invention shown in Examples 1 - 17. In the current comparative examples, either the tensile properties and toughness are poor or the polymer properties do not allow for enough parts to be made for testing. As can be seen by the high AD, the polymer powders formed in Comparative Examples 9 - 13 are dense. Dense powders result in parts with low specific gravity, low tensile strength, low % elongation, and low polymer toughness. Comparative Example 9 uses only 3 monomers (BPDA, PMDA, and ODA) in the composition. These examples demonstrate that all four monomers - BPDA, PMDA, PPD, and ODA - are needed to form a polymer with low powder density and high toughness. The copolymers of Comparative Examples 10 and 11 are synthesized from all 4 monomers and they exhibit sufficiently low apparent density (< 0.25 Ksi) but they show low strength, low elongation, and very low toughness. In both of these poor performing copolymer compositions, the mol % of PPD is significantly greater than the mol % of BPDA. Therefore, these examples demonstrate that for a higher toughness copolymer composition, the mol % of BPDA needs to be > (the mol % of PPD + 0.2).
[0193] Example 18
[0194] The copolymerized polyimide composition with 60 mol% BPDA, 60 mol% PPD, 40 mol% PMDA, and 40 mol% ODA contained 9 wt% graphite as a filler.
[0195] The polyamic acid of the copolymerized polyimide of this example was synthesized in the laboratory using a very similar method to that described in Example 1. 10.54 g of PPD and 13.01 g of ODA were dissolved in 600 g of anhydrous pyridine at 35 °C. The diamine solution was heated to 50 °C at which time 28.46 g of BPDA and 14.06 g of PMDA were simultaneously added to the reaction vessel to initiate the polymerization reaction. Any residual dianhydride in the weigh boat was rinsed into the polymerization reactor using 19.1 g of added pyridine.
[0196] After a 1 hour reaction time, the polymer was measured to have a M n and M w of 90,000 Dalton and 186,000 Dalton, respectively.
[0197] Into a clean high pressure Parr reactor was added 168.8 g of anhydrous pyridine. To this solvent tail was added 5.96 g of natural graphite of the 200-09 grade sold by Southern Graphite and dispersed by means of an anchor stirrer rotating at 200 rpm. The reactor was purged with nitrogen and the graphite-pyridine slurry was heated to 114 °C. Approximately simultaneously, 548.1 g of the PAA solution synthesized above was transferred to an ISCO syringe pump and heated to 70 °C. Once the temperature of the PAA solution in the pump was stable, the transfer of the PAA solution to the Parr reactor was initiated. The temperature of the imidization reaction was held constant at 114 °C throughout the PAA transfer. All of the PAA in the ISCO pump was transferred within 90 minutes. At the end of the PAA transfer, the PAA feed line from the pump was purged into the imidization reactor with 29.1 g of pyridine. As in Example 1, at the end of the PAA transfer, the contents of the imidizer were heated to 145 °C over 75 minutes after which the reactor was held at 145 °C for an additional 30 minutes. After this hold time, the imidization process was considered complete and the contents of the reactor were cooled to room temperature.
[0198] The particle size distribution D50 of the particles in the reaction slurry was measured to be 57.9 µm. The copolymerized polyimide slurry containing graphite was filtered, the filter cake was washed with acetone and then dried in a heated vacuum oven overnight to obtain a copolymerized polyimide resin containing 9 wt.% graphite.
[0199] Polymer powders were compression molded at room temperature to form green tensile bars, which were sintered at 405 °C as described in Example 1. The tensile properties of the sintered bars were also measured in the same manner as described in Example 1.
[0200] Table 15 shows the tensile strength, % elongation at break, and measured toughness of the copolymerized polyimides containing graphite. It is well known to those skilled in the art that the addition of solid fillers to any polymer will decrease its toughness. But even though the copolymer of this example contains 9% graphite filler and its toughness is decreased from the unfilled composition taught in Example 4, the filled copolymer still shows higher toughness than the unfilled homopolymers of BPDA-PPD and PMDA-ODA.
[0201] Table 15
[0202]
[0203] Example 19
[0204] A copolymerized polyimide containing 60 mol% BPDA, 60 mol% PPD, 40 mol% PMDA, and 40 mol% ODA was synthesized as described in Example 17. The imidization step was also very similar to that described in Example 17, except that this example added 0.5 g of Polyfil DL Kaolinite (supplied by KaMin, Inc.) along with 5.3 g of natural graphite to the 169.9 g of anhydrous pyridine tailings in the high pressure Parr reactor. For this reaction, 548.2 g of the copolymerized polyimide PAA solution was transferred to the imidization reactor over a 90 minute duration. The final composition of fillers in the copolymerized polyimide resin was 1 wt.% kaolinite and 9 wt.% graphite.
[0205] Tensile bars were made and tested from the filled copolymerized polyimide resin as described in Example 1. The tensile strength, % elongation, and toughness of the filled copolymerized polyimide resin are shown in Table 16.
[0206] Again, the filled copolymer of this example exhibited higher toughness than the unfilled homopolymers of BPDA-PPD and PMDA-ODA.
[0207] Table 16
[0208]
[0209] Example 20
[0210] A copolymerized polyimide composition having 60 mol% BPDA, 60 mol% PPD, 40 mol% PMDA, and 40 mol% ODA and containing 10 wt% graphite as a filler.
[0211] A copolymerized polyimide polyamic acid containing 60 mol% BPDA, 60 mol% PPD, 40 mol% PMDA, and 40 mol% ODA was polymerized in the same manner as described in Example 1. 7.03 g PPD and 19.51 g ODA were reacted with 18.97 g BPDA and 21.09 g PMDA in 624.1 g anhydrous pyridine.
[0212] The imidization process was carried out in the same manner as described in Example 17 in the presence of natural graphite. 5.9 g natural graphite was dispersed in 168.5 g anhydrous pyridine tail. 552.6 g of the copolymerized polyimide polyamic acid was added to the imidization reaction followed by 29 g of clean pyridine. After the imidization reaction was complete, the slurry was filtered, the filter cake was washed with acetone and then dried. Tensile bars were made from the filled resin and then tested for tensile properties.
[0213] The tensile strength of the filled copolymerized polyimide resin was 17,480 psi and the elongation at break was 12.76%.
[0214] Example 21 - 25
[0215] The current examples demonstrate the low friction and low wear properties of the graphite and kaolin filled copolymers of the present invention.
[0216] A copolymerized polyimide composition having different amounts of BPDA, PPD, PMDA, and ODA was polymerized using the same method described in Example 1. The copolymer polyamic acid solution so produced was converted to graphite and kaolin filled polyimide powders and parts using the method described in Example 18. Two different types of graphite were used for these examples. The first was natural graphite 200-09 sold by Southwestern Graphite and the second was synthetic graphite Asbury 4767 sold by Asbury Carbons Company.
[0217] The compositions of the copolymers produced are shown in Table 17 and the tensile properties of these polymers are shown in Table 18.
[0218] Table 17
[0219]
[0220] Table 18
[0221]
[0222] The copolymer powders of Examples 21–25 were compressed and molded at 80,000 psi to form 1” diameter discs with a thickness between 6 and 6.5 mm. Three discs were formed for each composition. The green discs were sintered using the same sintering cycle and temperature as all the stretch bars used in the previous examples. After sintering, the discs were machined to form test blocks for a tight fit with the steel ring of the Falex tester. The machined blocks were mounted onto the sample holder on the Falex tester and then tested under different PV conditions as described in the previous section. Multiple tests were performed for each composition. One test was conducted for 24 hours at a constant PV of 100,000 psi ft / min, and a second test was conducted at 300,000 psi. Tribological and abrasion properties of the filled copolymer at 100,000 psi ft / min were performed, and another test was conducted at progressively increasing PV conditions (PV limit test) until the sample failed or the test was terminated due to an exponential increase in temperature caused by frictional heat generation. At the end of the constant PV test, dimensional wear, weight-based wear factor, coefficient of friction, and steady-state ambient temperature due to frictional heat generation were recorded. The tribological and abrasion properties of the filled copolymer at 100,000 psi ft / min are shown in Table 19, and the tribological and abrasion properties at higher PV conditions of 300,000 psi ft / min are shown in Table 20. The PV limit conditions, under which the PV limit test was terminated due to an exponential increase in temperature caused by frictional heat generation, are also shown in Table 18.
[0223] Table 19
[0224]
[0225] Table 20
[0226]
[0227] Compare Examples 14-15
[0228] DuPont uses the brand name Vespel ® SP-21 manufactured a graphite-filled homopolymer of PMDA-ODA. The average tensile strength and % elongation of this polymer grade are 10,500 psi and 7.5%, respectively.
[0229] DuPont also manufactures graphite-filled polymers derived from BPDA and PPD, under the trade name Vespel. ® SCP-50094 is for sale. The average tensile strength and % elongation of this class are 20,000 psi and 4.0%, respectively.
[0230] Powdered forms of SP-21 polymer and SCP-50094 polymer were compression molded at 80,000 psi to form a plurality of 1” diameter, 6 mm thick discs. These discs were machined into friction and wear test blocks for a Falex block on ring tester. Both grades of polymer were tested for friction and wear at 100,000 psi ft / min, 300,000 psi ft / min, and PV limit testing.
[0231] The friction and wear performance of both SP-21 and SCP-50094 at 100,000 psi ft / min is shown in Table 21, and the friction and wear performance of both polymers at 300,000 psi ft / min and PV limit is shown in Table 22. The filled copolymers of the present invention, as exemplified by Examples 21-25, outperform both SP-21 in terms of tensile properties as well as friction and wear performance.
[0232] Table 21
[0233]
[0234] Table 22
[0235] .
Claims
1. A polyimide composition comprising: Particles of polyimide polymers derived from (i) ODA, (ii) PMDA, (iii) PPD, and (iv) BPDA monomers. in, When the polyimide composition consists of particles of the polyimide polymer, the polyimide composition has an apparent density of ≤ 0.25 g / cm³.
2. The polyimide composition of claim 1, wherein, Parts made from the polyimide composition have a toughness of ≥ 0.80 Ksi and a strength of ≥ 1.38 g / cm³. 3 Specific gravity, or toughness ≥ 0.80 Ksi and ≥ 1.4 g / cm³ 3 The specific gravity of the polyimide composition is determined by the composition of particles of the polyimide polymer.
3. The polyimide composition according to claim 1, wherein, The sum of the molar fractions of BPDA and PMDA in the particles of the polyimide polymer is about 1, and the sum of the molar fractions of PPD and ODA in the particles of the polyimide polymer is about 1, wherein the relationship between the molar fraction of BPDA and the molar fraction of PPD in the particles of the polyimide polymer is in the range of PPD - 0.2 < BPDA < PPD + 0.
2.
4. The polyimide composition according to claim 1, comprising: Polyimide comprising one or more of the following repeating units 、 、 、 and 。 5. The polyimide composition according to claim 1, wherein, The polyimide composition includes a filler, wherein the filler is present at up to 75% (w / w) by weight of the polyimide composition.
6. The polyimide composition according to claim 5, wherein, The filler is graphite or clay.
7. A part comprising: a polyimide composition according to any one of claims 1 to 6.
8. The part according to claim 7, wherein, The polyimide composition is molded to form the part.
9. The part according to claim 7 or 8, wherein, The components are clutch rollers, sealing rings, spherical washers, compressor seals, lip seals, valve seats, ball bearing cages, and drive discs.
10. A method for manufacturing a polyimide composition, comprising: (i) ODA, (ii) PMDA, (iii) PPD, (iv) BPDA and (v) solvent were combined under time and conditions sufficient to form a reaction product comprising polyamide and solvent; The reaction products were heated at a temperature and time sufficient to remove water and form polyimide particles. The resulting polyimide particles are filtered and washed. The washed polyimide particles are dried to form a polyimide composition, wherein the polyimide composition comprises the polyimide particles; When the polyimide composition consists of particles of a polyimide polymer, the polyimide composition has an apparent density of ≤ 0.25 g / cm³.
Citation Information
Patent Citations
Polyamide-acids, compositions thereof, and process for their preparation
US3179614A
Aromatic polyimide particles from polycyclic diamines
US3179631A
Process for preparing finely divided polyimide particles of high surface area
US3249588A
Oxidatively stable rigid aromatic polyimide compositions and process for their preparation
US5886129A